Teacher’s Technology Integration ELT Based on SAMR Model in Writing Skill - Dani Fathurohman Fathurohman; Andi Dian Rahmawan (JEdu: Journal of English Education, 2021)
This  study  is  aimed  to  know  the technology categories integrated by the teacher and classify the teacher’s technology  integration  level. Descriptive qualitative  is used  to describe  the  result of  this  study. The data is collected through interview and observation at SMA N 1 SENTOLO. It is focused on the teaching of writing. the subject of this research were 2 teacher. The data were transformed into descriptive text and interviewed transcripts.  The data analysis used reduction data, the data display, and conclusion drawing or verification.  The data validation used triangulation of technique of collecting data and triangulation of source of data.The source of data taken from interview . Based on the result of finding and discussion, it is found that the teacher integrated  more than  four technology  categories  which  are  word  processing, spreadsheet  software,  organizing  and  brainstorm,  multimedia,  and web  resources.  The  teacher  integrated  those technologies  in  teaching listening, reading and writing skill. While  the  activities is analysed  based  on  SAMR model  to  know  the teacher’s  technology  integration .The  result  shows that  the  teacher  is  on  the  augmentation  level  in  teaching writing  skill, which  the  teacher  uses word  processing with  additional  functions  like spell  check,  cut,  and  paste  the  documents.  Therefore,  the  teacher  is classified on passing the substitution level, because the teacher is on the augmentation  level,  which  integrates  technology  as  a  direct  tool substitute, with functional improvement.